Trauma admissions among street children at a tertiary care hospital in north-western Tanzania: a neglected public health problem - Chalya, Phillipo L.; Hauli, Kiyeti A.; Kayange, Neema M.; Mweteni, Wemaeli; Kapesa, Anthony; Ngallaba, Sospatro E. (Tanzania Journal of Health Research, 2016)
Background: Trauma among street children is an emerging but neglected public health problem in most low and middle income countries. This study was conducted to determine the incidence, etiological spectrum, injury characteristics and treatment outcome among street children and to identify the predictors of the outcome of these patients at Bugando Medical Centre in Mwanza, Tanzania. Methods: The study included street children aged <18 years. Routine investigations including haematological, biochemical and imaging were performed on admission. The severity of injury was determined using the Kampala Trauma Score II. Data on patient’s characteristics, circumstances of injury, injury characteristics, treatment offered, outcome variables, length of hospital stay and mortality were collected using a questionnaire. Results: A total of 342 street children (M: F = 6.8: 1) representing 11.5% of all paediatric injury patients were studied. The modal age group was 11-15 years (median = 12 years) accounting for 53.2% (n=182) of the patients. Assault was the most frequent (73.7%) cause of injury. More than three quarter of injuries occurred along the street. Most of patients (59.1%) presented late (>24 hours) after injury. Blunt injuries were the most common (76.0%) mechanism of injuries. Musculoskeletal (30.8%) and head (25.3%) were the most frequent body regions affected. Soft tissue injuries were the most common type of injuries affecting 322 (94.2%) cases. Majority of patients (96.5%) underwent surgical treatment of which wound debridement (97.6%) was the most common surgical procedure performed. Complication rate was 39.5%. The median hospital stay was 6 days. Mortality rate was 13.5% and it was significantly associated with injury-arrival time (OR =2.4, 95%CI (1.3-5.6), p = 0.002), severe injury (Kampala Trauma Score <6) (OR = 3.6, 95%CI (2.5-7.9), p = 0.001), severe head injuries (OR= 5.1, 95%CI (4.6 – 8.2), p =0.012) and surgical site infection. Conclusion: Trauma among street children is an emerging but neglected epidemic in Tanzania and contributes significantly to high morbidity and mortality. Assault was the most frequent cause of injury. Urgent preventive measures targeting at reducing the occurrence of assault is necessary to reduce the incidence of trauma among street children in this region.